Authenticity in the Pursuit of Mutuality During Crisis. (21st June 2022) - Nayani, Rachel; Baric, Marijana; Patey, Jana; Fitzhugh, Helen; Watson, David; Tregaskis, Olga; Daniels, Kevin
Abstract: Employee wellbeing activities constitute a space for organizations to realize a shared agenda with employees, and therefore a means to pursue mutuality. The pursuit of mutuality draws on assumptions of reciprocity in social exchange theory (SET) but is dynamic and put under pressure by external shocks. The first UK COVID‐19 lockdown provided the setting to explore how organizations addressed employee wellbeing concerns under conditions of crisis. Using qualitative data from five organizations, we identify authenticity‐building, which is the constellation of past and present activities through which organizations channel efforts to be authentic in their concern for employees. Attributions of authenticity emerge as fundamental to authenticity‐building, while authenticity work (the organization noticing, understanding and acting on shifts in interests) is enabled by dialogic processes. Authenticity‐building shifts the quality of the exchange relationship to allow for mutual benefits and is therefore a vital and dynamic component of mutuality. Our findings contribute to the mutuality literature by providing a theoretically embedded extension of SET and show how organizations may become more (or less) authentic within the context of the employment relationship. We highlight the complexity of organizational endeavour for mutuality and show how mutuality need not be compromised during external shocks.